Privatisation/Libéralisation des filières cotonnières en Afrique. Quels gagnants ? Quels perdants ? - Tazi S. (Biotechnologie, Agronomie, Société et Environnement, 2006)
Privatisation/Liberalization in the Africa cotton sectors. Who wins ? Who looses ? Questions on the methodologicalchallenges related to the evaluation of the impact of liberalization/privatisation introduce the level of diffi culty and the limits ofthe different methods classically used. Several complementary approaches based on the neo-institutional economy, which putthe institutions and the mechanisms of coordination in the heart of the sector analysis, as well as common and public goods, aresuggested. These methods integrate qualitative factors and call in question the bases even of what chaired the principles of theprivatisation/liberalization, namely the only coordination by the market. The methodological orientations result from a studyconducted in the framework of a monitoring mechanism for the cotton sectors of 6 francophone African countries called «Resocot».The fi rst objective was helping the discussion between the stakeholders and sharing the experiences and institutional innovationsbetween the different countries. A collaboration with other projects conducted in the Eastern African countries allowed to identifythe limits of the initial model as conceived by the World Bank. Dedicated to support the competition and better prices to theproducers, the outcomes of the process of privatisation/liberalisation correspond to a less consideration of the farmer constraints.Indeed, it dismantled mechanisms of coordination which took decades to be developed and which made it possible to compensatethe failures mechanisms of coordination by the State or the market and to ensure a certain level of safety. Finally, we suggest a newand broad vision of cotton sectors integrating social and human issues and the mechanisms of coordination that they «created»through several years of experience, to overcome the failures of their models of organization whatever they are.